Pengaturan Hak Asasi Manusia bagi Perempuan Indonesia Pasca Amandemen UUD 1945 - Saputri, Ravita Mega; Rinenggo, Alil (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
This study aims to find out about human rights arrangements, especially for women after the amendments to the 1945 Constitution. This research uses a qualitative approach in the nature of literature study. Researchers also reviewed several books written by experts, journals, articles related to this study. The data analysis process used in this study includes data reduction, data presentation, verification and conclusions. The results of this study indicate that post-amendment human rights are regulated in articles 28A to 28J of the 1945 Constitution. Implementation of human rights arrangements has not been fully implemented in accordance with the legal basis in Indonesia, there are still many violations of human rights, especially women's rights regarding the issue of inequality socio-cultural and violence against women. If this is not taken seriously, it is feared that Indonesia will be threatened as a country that is not committed to implementing the constitution so that there must be strengthening of women's rights and increased awareness of gender equality which is supported by all parties.Keywords: human rights, women, amendments to the 1945 Constitution